Discursive Practice Used in Sermons of Waibu Moi Churches in Jayapura - Berthin Samuati Banga; Lewi Kabanga'; Simon Tabuni (Hasanuddin University, 2023)
Sermon has vital roles in educating the people of Papua in Jayapura. It is considered one of the legal ways effect the attitude of Papuan Christianity. Sermon conducted in Waibu Moi Churches of Jayapura contains power of language to ensure the life as Christianity. The power of language used by the preacher is seen by using discursive text analysis. The goal of this study is to present the language power used by the preacher in Waibu-Moi Churches of Jayapura. The method applied in this study was descriptive qualitative. The data was taken from 5 churches which have good management by using recording technique. The techniques of analyzing data were transcription, reducing, data display, and analysis. The Analysis of data used the theory of Fairclough, discursive dimensions, combined with the analysis of formal aspect of language namely experiential analysis. The results of this analysis show that the power of language used by the preachers in Waibu Moi churches are generally forms the features of analogy , cause and effect, affirmation statements, and code of language in mixing and switching.